2005
DOI: 10.1007/s00268-005-7719-y
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of an Estimation of Physiologic Ability and Surgical Stress (E‐PASS) Scoring System to Predict the Incidence of Postoperative Complications in Gastrointestinal Surgery

Abstract: Surgical intervention induces various host responses to maintain homeostasis. When postoperative inflammation is intense and persists for a long time, postoperative complications may occur, sometimes developing into multiple organ failure. Therefore, it is very important to assess surgical stress and predict the risk of morbidity and mortality. Using a new scoring system, an estimation of physiologic ability and surgical stress (E-PASS) scoring system, surgical stress following gastrointestinal surgery was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 25 publications
1
36
1
1
Order By: Relevance
“…Several cohort studies performed by the authors as well as other researchers have demonstrated reproducible outcomes in predicting adverse postoperative events [14][15][16][17][18][19][20]. We recently modified this system and designated this revised version mE-PASS.…”
Section: Introductionmentioning
confidence: 99%
“…Several cohort studies performed by the authors as well as other researchers have demonstrated reproducible outcomes in predicting adverse postoperative events [14][15][16][17][18][19][20]. We recently modified this system and designated this revised version mE-PASS.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported its usefulness in various surgical fields (Tang et al, 2007;Yamashita et al, 2006;Oka et al, 2005). E-PASS consists of three items: PRS, SSS, and CRS.…”
Section: Discussionmentioning
confidence: 99%
“…A los factores de riesgo reconocidos por Copeland 17 , le siguió la estructuración de un sistema que incorporó diversos parámetros operatorios: Stress) que puede ayudar a planificar un tratamiento quirúrgico 23,24 25 . Con el ACS se ha construido un programa nacional validado, basado en resultados y ajustado por riesgo, colocando a disposición una herramienta de cálculo del riesgo quirúrgico para un paciente particular frente a una cirugía determinada.…”
Section: Sistemas Predictivos De Morbilidad Y Mortalidad Postoperatoriaunclassified